2017
DOI: 10.1021/acs.joc.6b02804
|View full text |Cite
|
Sign up to set email alerts
|

1,2,3-Triazolium-Based Peptoid Oligomers

Abstract: The cis-directing effect of the 1,2,3-triazolium-type side chain was studied on dimeric peptoid models with various patterns: αα, αβ, βα and ββ. Low influences of the sequence and of the solvent were observed, the cis conformation of the amide carrying the triazolium ranging from 83 to 94% in proportion. The synthesis of peptoid homooligomers with four or eight pendant 1,2,3-triazolium side chains is described. α-, β- and α,β-peptoids carrying propargyl groups were subjected to CuAAC reaction using alkyl azide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 60 publications
2
29
0
Order By: Relevance
“…The cis/trans ratio of the terminal acetamide was determined for all the trimer peptoids 4 ‐ 9 by 1 H NMR integration of singlets corresponding to the acetyl CH 3 protons (Figure ). According to previous studies, the protons of trans peptoid acetamides are deshielded which results in a chemical shift of ˃2 ppm. On the contrary, it was observed that the protons of cis acetamides display a chemical shift of <2 ppm.…”
Section: Resultsmentioning
confidence: 86%
“…The cis/trans ratio of the terminal acetamide was determined for all the trimer peptoids 4 ‐ 9 by 1 H NMR integration of singlets corresponding to the acetyl CH 3 protons (Figure ). According to previous studies, the protons of trans peptoid acetamides are deshielded which results in a chemical shift of ˃2 ppm. On the contrary, it was observed that the protons of cis acetamides display a chemical shift of <2 ppm.…”
Section: Resultsmentioning
confidence: 86%
“…It is important to note that in the course of antimicrobial peptoid design, short oligomers were often poorly active except those incorporating the dehydroabietyl moiety or a long alkyl tail . The potency of peptoid 3 may be due to the structuring effect of the triazolium group . Preliminary CD studies on this series showed that peptoids 2 , 3 , and 9 present the characteristic CD signature of the PPI‐like helix of peptoids with two minima at 203 and 220 nm (Figure ) .…”
Section: Figurementioning
confidence: 95%
“…[21] The potency of peptoid 3 may be due to the structuring effect of the triazolium group. [14,16] Preliminary CD studies on this series showed that peptoids 2, 3,a nd 9 present the characteristicC Ds ignature of the PPI-like helix of peptoids with two minima at 203 and 220 nm (Figure 2). [8] The lower band intensity for triazolebased hexapeptoid 2 compared with the triazolium-based hexapeptoid 3 is indicative of helical structure stabilization by the triazoliums.…”
mentioning
confidence: 88%
See 2 more Smart Citations